(untitled) (Scientific journal of the Fergana State University, 2023)
The sol-gel method was used to synthesis rhombic-shaped TiO2 colloidal particles by combining organic solvents ethanol and acetonitrile in a 3:1 mol ratio. It is noted that the process includes stages of hydrolysis and polycondensation. Scanning electron microscopy and atomic force microscopy were used to determine the morphology and sizes of synthesized colloidal TiO2 particles. The synthesized particles have a diameter of 250-350 nm and a thickness of 15-30 nm.